2016
DOI: 10.3390/nu8040236
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Autism Spectrum Disorder: A Literature Review

Abstract: Low vitamin D status in early development has been hypothesised as an environmental risk factor for Autism Spectrum Disorder (ASD), given the concurrent increase in the prevalence of these two conditions, and the association of vitamin D with many ASD-associated medical conditions. Identification of vitamin D-ASD factors may provide indications for primary and secondary prevention interventions. We systematically reviewed the literature for studies on vitamin D-ASD relationship, including potential mechanistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 197 publications
0
71
0
Order By: Relevance
“…Low vitamin D status during pregnancy or childhood has also been associated with autism [176]. Severe maternal hypothyroxinaemia during early pregnancy has also been linked to an increased incidence of autism in the offspring [177].…”
Section: Autism Genes Are Targeted By Relevant Hormones and Transmittmentioning
confidence: 99%
“…Low vitamin D status during pregnancy or childhood has also been associated with autism [176]. Severe maternal hypothyroxinaemia during early pregnancy has also been linked to an increased incidence of autism in the offspring [177].…”
Section: Autism Genes Are Targeted By Relevant Hormones and Transmittmentioning
confidence: 99%
“…In ASD studies, although omega-3-fatty acid supplementation had no significant beneficial effects in adult patients [37], another study on children have shown significant improvements in social and communication responses [38]. Among vitamins, vitamin B6 and magnesium [39], and vitamin D [40], have shown beneficial effects in few studies, while others such as vitamin A, and vitamin B12 and folic acid have been proposed as potential treatment options for ASD. Minerals such as magnesium [39], iron [41], and zinc [42], have also been recommended for nutritional therapies in ASD.…”
Section: Supplementsmentioning
confidence: 99%
“…Lower nocturnal melatonin or melatonin metabolite concentrations have been observed in autism and melatonin treatment improves sleep quality and daytime behaviour in autistic subjects [66,67].Low vitamin D status during pregnancy or childhood has also been associated with autism [68]. Severe maternal hypothyroxinaemia during early pregnancy has also been linked to an increased incidence of autism in the offspring [69].…”
Section: Autism Genes Are Targeted By Relevant Hormones and Transmittmentioning
confidence: 99%